Frequency and Predictors of Headache in the First 12 Months After Traumatic Brain Injury: Results from CENTER-TBI - Howe, Emilie Isager; Andelic, Nada; Brunborg, Cathrine; Zeldovich, Marina; Helseth, Eirik; Skandsen, Toril; Olsen, Alexander; Fure, Silje CR; Theadom, Alice; Rauen, Katrin; Madsen, Benedikte Å; Jacobs, Bram; et al. (BMC, 2024)
BACKGROUND: Headache is a prevalent and debilitating symptom following traumatic brain injury (TBI). Large-scale, prospective cohort studies are needed to establish long-term headache prevalence and associated factors after TBI. This study aimed to assess the frequency and severity of headache after TBI and determine whether sociodemographic factors, injury severity characteristics, and pre- and post-injury comorbidities predicted changes in headache frequency and severity during the first 12 months after injury. METHODS: A large patient sample from the Collaborative European NeuroTrauma Effectiveness Research in Traumatic Brain Injury (CENTER-TBI) prospective observational cohort study was used. Patients were stratified based on their clinical care pathway: admitted to an emergency room (ER), a ward (ADM) or an intensive care unit (ICU) in the acute phase. Headache was assessed using a single item from the Rivermead Post-Concussion Symptoms Questionnaire measured at baseline, 3, 6 and 12 months after injury. Mixed-effect logistic regression analyses were applied to investigate changes in headache frequency and associated predictors. RESULTS: A total of 2,291 patients responded to the headache item at baseline. At study enrolment, 59.3% of patients reported acute headache, with similar frequencies across all strata. Female patients and those aged up to 40 years reported a higher frequency of headache at baseline compared to males and older adults. The frequency of severe headache was highest in patients admitted to the ICU. The frequency of headache in the ER stratum decreased substantially from baseline to 3 months and remained from 3 to 6 months. Similar trajectory trends were observed in the ICU and ADM strata across 12 months. Younger age, more severe TBI, fatigue, neck pain and vision problems were among the predictors of more severe headache over time. More than 25% of patients experienced headache at 12 months after injury. CONCLUSIONS: Headache is a common symptom after TBI, especially in female and younger patients. It typically decreases in the first 3 months before stabilising. However, more than a quarter of patients still experienced headache at 12 months after injury. Translational research is needed to advance the clinical decision-making process and improve targeted medical treatment for headache. TRIAL REGISTRATION: ClinicalTrials.gov NCT02210221.
Keywords: Brain trauma; Observational study; Post-traumatic headache; Secondary headache disorders; Brain trauma; Observational study; Post-traumatic headache; Secondary headache disorders; CENTER-TBI Participants and Investigators; 32 Biomedical and Clinical Sciences; 3202 Clinical Sciences; Neurosciences; Clinical Research; Brain Disorders; Pain Research; Headaches; Traumatic Head and Spine Injury; Traumatic Brain Injury (TBI); Chronic Pain; Physical Injury - Accidents and Adverse Effects; Injuries and accidents; Neurological; 0604 Genetics; 1103 Clinical Sciences; Neurology & Neurosurgery; 3202 Clinical sciences; 3209 Neurosciences; Aged; Brain Injuries, Traumatic; Comorbidity; Emergency Service, Hospital; Female; Headache; Humans; Male; Prospective Studies; Male; Humans; Female; Aged; Prospective Studies; Brain Injuries, Traumatic; Headache; Comorbidity; Emergency Service, Hospital; Humans; Headache; Prospective Studies; Comorbidity; Aged; Emergency Service, Hospital; Female; Male; Brain Injuries, Traumatic